1992
DOI: 10.1002/jat.2550120209
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of citrinin‐induced dysfunction of mitochondria. I. Effects on respiration, enzyme activities and membrane potential of renal cortical mitochondria

Abstract: Citrinin depresses the phosphorylation efficiency of rat renal cortical mitochondria, as inferred from the decrease of the respiratory control coefficient (RC) and ADP/O ratios. The transmembrane potential (delta psi) developed by energized mitochondria and the depolarization upon ADP addition are also decreased. Citrinin (1.0 mM) inhibits almost all enzymes linked to the respiratory chain and increases the activity of succinate cytochrome c reductase and succinate oxidase (coupled). Malate and glutamate dehyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

1992
1992
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 21 publications
0
32
0
2
Order By: Relevance
“…The LLC-MK2 cells decreased the most and the MDBK cells showed distinct morphological alterations. Studies on the mechanism of citrinininduced dysfunction of the rat mitochondria were undertaken (16)(17)(18)(19). Citrinin depressed the phosphorylation efficiency of renal cortical mitochondria and inhibited most of the enzymes of the respiratory chain of the rat renal cortical and liver mitochondria.…”
Section: Toxic Effects and Mode Of Actionmentioning
confidence: 99%
“…The LLC-MK2 cells decreased the most and the MDBK cells showed distinct morphological alterations. Studies on the mechanism of citrinininduced dysfunction of the rat mitochondria were undertaken (16)(17)(18)(19). Citrinin depressed the phosphorylation efficiency of renal cortical mitochondria and inhibited most of the enzymes of the respiratory chain of the rat renal cortical and liver mitochondria.…”
Section: Toxic Effects and Mode Of Actionmentioning
confidence: 99%
“…There are dozens of reports showing that high doses of citrinin act as a cytotoxin and nephrotoxin (Ambrose and DeEds, 1946;Friis et al, 1969;Krogh et al, 1970;Scott et al, 1972;Nelson et al, 1985;Aleo et al, 1991;Chagas et al, 1992aChagas et al, , 1992bDa Lozzo et al, 1998;Abramson et al, 2001;Liu et al, 2003;Yu et al, 2006;Bouslimi et al, 2008). In contrast, our results indicate a new role/implication for low-dose citrinin in health and disease.…”
Section: Discussionmentioning
confidence: 41%
“…The toxicities of citrinin have been frequently reported as cytotoxic (50-220 μM, 24-72 hr as LC 50 , which depends on cell type) (Liu et al, 2003;Yu et al, 2006;Bouslimi et al, 2008) and nephrotoxic via swelling of the kidney and acute tubular necrosis (50-134 mg/kg orally as LD 50 , which depends on species) (Ambrose and DeEds, 1946;Friis et al, 1969;Krogh et al, 1970). The mechanism of citrinin toxicity is thought to involve mitochondrial dysfunction (Aleo et al, 1991;Chagas et al, 1992aChagas et al, , 1992bDa Lozzo et al, 1998). Furthermore, citrinin affects intracellular calcium level (Berndt et al, 1984;Chan, 2008;Klarić et al, 2012) so that citrinin has the potential to influence the cellular events regulated by calcium influx.…”
Section: Introductionmentioning
confidence: 99%
“…While it is also known as a hepato-nephrotoxin in a wide range of species (Berndt, 1990), in vitro studies have demonstrated that citrinin produced multiple effects on renal mitochondrial function and macromolecule biosynthesis that ultimately resulted in cell death (Chagas et al, 1992(Chagas et al, , 1995. Citrinin has been found to disrupt renal function in all species in which it has been tested (Berndt, 1990).…”
Section: Discussionmentioning
confidence: 99%